Analysis of Macular Retinal Thickness and Microvascular System Changes in Children with Monocular Hyperopic Anisometropia and Severe Amblyopia. (17th January 2022) - Liu, Lin-Lin; Wang, Yu-Chuan; Cao, Miao; Liu, Fang; Zhang, Shuang; Liu, Jing; Liu, Jin-Chang; Xie, Lian-Feng; Wang, Hui
Abstract : Objective . To study the changes of macular retinal thickness and microvascular system in children with monocular hyperopic anisometropia and severe amblyopia using optical coherence tomography angiography (OCTA) and to explore the value of OCTA in the diagnosis and treatment of amblyopia. Methods . Thirty-two children with monocular hyperopic anisometropia and severe amblyopia who were treated in the Department of Ophthalmology of the First Affiliated Hospital of Gannan Medical College from January 2020 to December 2020 were included in the study. Eyes with amblyopia (n = 32 ) served as the experimental group, and the contralateral healthy eyes (n = 32 eyes) served as the control group. All children underwent comprehensive ophthalmological examination including slit lamp, eye position, visual acuity, optometry, eye movement, intraocular pressure, ocular axis, and fundus examination to rule out organic lesions. Macular 6   mm × 6   mm scans were performed on both eyes of all subjects by the same experienced clinician using an OCTA instrument. After ImageJ processing, the vessel density, inner layer, and full-layer retinal thickness (RT) of superficial retinal capillary plexus (SCP) were obtained. All data were analyzed by SPSS21.0 software, and a paired t -test was used for comparison between groups. P < 0.05 was considered to indicate statistical significance. Results . The vessel densities of macular SCP in the amblyopia and control groups were 47.66 ± 2.36 % and 50.37 ± 2.24 % in the outer superior, 49.19 ± 2.64 % and 51.44 ± 2.44 % in the inner inferior, 49.63 ± 2.51 % and 51.41 ± 3.03 % in the outer inferior, and 45.56 ± 3.44 % and 50.44 ± 3.52 % in the outer temporal regions, respectively. The vessel density of macular SCP in the amblyopia group was significantly lower than that in contralateral healthy eyes in the outer superior, inner inferior, outer inferior, outer temporal, and central regions. There was no significant difference between the two groups in the inner superior, inner nasal, outer nasal, and inner temporal regions. The macular RT in the amblyopia group and the control group is 90.38 ± 6.09   μ m and 87.56 ± 5.55   μ m in the outer temporal, respectively. The RT in the macular inner layer in the outer temporal region of the amblyopia group was thicker than that of the control group (P < 0.05 ). There was no significant difference in the other eight regions between the two groups. The whole macular RT in the amblyopia group was thicker than that in the control group in nine regions, and the central area of macular RT in the amblyopia and control groups was 229.06 ± 6.70   μ m and 214.50 ± 10.36   μ m, respectively. Conclusion . The OCTA results showed the overall RT of macula in 9 areas in the amblyopia group was thicker than that in the control group, which could show that the macular retinal thickness can be a potential way to distinguish the children with monocular hyperopic anisometropia and severe amblyopia.